Implementation of Network Automation using Ansible to Configure Routing Protocol in Cisco and Mikrotik Router with Raspberry PI: Array - Muhammad Fauzi Islami; Purnawarman Musa; Missa Lamsani (Jurnal Ilmiah Komputasi, 2020)
Network Engineering is never separated with configuration which is the main task must be committed in the purpose to put it into function. As we know, to configure some devices either server, switch, or router have some methods if we ob-serve by how we communicate to the system themselves. We can use the console port to communicate with, using telnet to communicate remotely, or even using SSH if we want to communicate remotely and also securely with all of the in-formation is encrypted. Generally, the conventional method such as the methods has just explained before is always be used. The problem has not come yet since there are just 1 until 5 devices, but how about 100 devices ? We have to log in to the network devices one by one. It is exhausting and very inefficient in time. This paper is illustrating a new methods in configuring network devices by using automation, reducing time for equipment configuration and easier to maintenance. It reduces human error in configuration syntaxes and how the way the device is configured. The innovation is going to make it happen. There are tools to do this tasks such as, Ansible and Terraform. In this paper, Ansible is chosen because of its simplicity.